Efektivitas Peran Search for Common Ground dalam Menangani Kejahatan Kemanusiaan terhadap Perempuan dan Anak-Anak Korban Konflik Poso 2009-2016 - Purnasanti, Linda Uji; Windiani, Reni; Pattipelohy, Shary Charlotte (Journal of International Relations, 2018)
The high number of casualties among women and children encouraged SFCG (Search For Common Ground) to participate in dealing with the crimes against humanity upon them due to Poso conflict 2009-2016. This study aims to determine the effectiveness of SFCG's role in handling the issue by using qualitative research methods. The role of SFCG as an INGOs (International Non-Government Organizations) could be explained by using Nelson's indicator to determine the role of International Organization in conflict and peace which is also supported by Galtung's conflict resolution theory of peacebuilding. The results of this study found that SFCG's role in dealing with the crimes of humanity on women and children victims of Poso conflict during 2009-2016 was considered effective and should be an alternative againts similar social issues to involving internal and external organizations from various institutions.